Transformasi Aktivitas Mengamen melalui Media Digital: Studi Kualitatif pada Pengamen TikTok Live di Waru Sidoarjo - Adinda Dyah Pitaloka; Dera Nathasia; Theofilus Devine Imanuel; Willery Setia Labajo; Tan Evan Tandiyono (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The phenomenon of TikTok Live buskers illustrates how street-performing activities traditionally conducted in public spaces have shifted into the digital environment through social media platforms. The live streaming feature enables performers to reach broader audiences, interact directly with viewers, and generate income through virtual gifts. The purpose of this study is to explore the transformation of busking activities from public spaces to digital platforms, examine the interactions between performers and audiences, and explore the meaning of virtual gift-giving within TikTok Live. Drawing upon a qualitative case study methodology, this research was undertaken in Waru District, Sidoarjo Regency, to facilitate a nuanced understanding of the phenomenon under examination. Data collection was carried out between March and June 2026. Empirical data were generated through semi-structured interviews, direct observation, and document analysis, and subsequently interpreted using the interactive analytical framework developed by Miles, Huberman, and Saldaña. The results indicate that TikTok Live functions as a viable digital space through which performers can broaden their audience base, cultivate an online presence, and derive financial benefits from audience-contributed virtual gifts. Beyond their economic value, virtual gifts are interpreted as forms of appreciation, support, and recognition of the performers’ creativity. The study demonstrates that the migration of busking activities into digital spaces has reshaped not only the economic practices of performers but also the nature of audience-performer relationships, giving rise to novel patterns of social interaction within the digital media landscape.